Laser sintering 3D printing polyamide powder
Through deep cold grinding and sieving technology, combined with specific proportions of polyamide, polyolefin and reinforcing fibers, 3D printed polyamide powder suitable for laser sintering is prepared, which solves the problems of poor sphericality and irregular morphology of the powder in the prior art, and achieves high fluidity and fillability. The processed products have smooth outer surfaces and no defects such as internal cavity and warping.
Patent Information
- Application Number
- CN202411638516.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-17
- Publication Date
- 2025-03-14
AI Technical Summary
It is difficult to prepare high-flow polyamide powders with the advantages of polyamide and polyolefin, resulting in problems such as warping and uneven surfaces in laser sintering 3D printing.
Through deep cold grinding and sieving technology, polyamide powder with a specific particle size distribution is prepared, and a specific proportion of polyamide, polyolefin and reinforcement fiber are mixed to form a 3D printed polyamide powder suitable for laser sintering.
The polyamide powder has uniform particle size distribution, good fluidity and filling properties, and the products obtained by SLS processing have smooth outer surfaces and no internal cavity and warping defects.
Smart Images

Figure BDA0005137794190000041 
Figure BDA0005137794190000051 
Figure BDA0005137794190000061
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of additive manufacturing, and specifically relates to laser sintering 3D printing polyamide powder. Background Art
[0002] Selective Laser Sintering (SLS) is one of the common 3D printing technologies. This technology uses the principle of CO2 laser irradiation powder layer sintering. Under computer control, it selectively sintered according to the contour of the sintered part of the equipment, and piled up the powder layer by layer to form a shape. The powder in the unsintered area serves as a support layer to support the sintered part without adding additional support. This technology has fast printing speed, high precision, low energy consumption and high utilization rate.
[0003] Polyamide (PA for short) is a kind of synthetic polymer material with excellent properties such as stable thermal properties, excellent mechanical properties, high fluidity, low static electricity, low water absorption, and moderate melting point. It is a widely used raw material for preparing SLS powder, but polyamide is expensive; in terms of cost, polyolefins are more attractive, they are cheap and show electrical insulation properties, and have chemical resistance and heat resistance. However, compared with polyamide, polyolefins generally have mediocre mechanical properties, such as mediocre fluidity, slow cooling cycle time, low elongation at break, and low thermal conductivity and low thermal diffusivity. Due to the presence of multiple crystalline phases, the processing window of polyolefins is narrower than that of polyamide, and it is difficult to avoid local bulges / warping problems during the printing process. The above-mentioned shortcomings severely limit the application of these two types of polymers as single materials in the field of laser sintering 3D printing. In the related art, there are few high-fluidity powders suitable for SLS processing based on polyamide and polyolefin composite high-resolution material systems.
[0004] There are four methods for preparing laser sintering 3D printing polyamide powder in industrial applications: mechanical crushing, solvent precipitation, direct polymerization, and thermally induced phase separation. Among them, the thermally induced phase separation method is in the research stage; the preparation processes of the solvent precipitation method and the direct polymerization method are complex and difficult to produce on a large scale. In comparison, the mechanical crushing method does not require chemical solvents, has a simple preparation method and is more suitable for large-scale production in industry. The mechanical crushing method usually uses liquid nitrogen or carbon dioxide as a cold source, and the temperature reaches below the brittle temperature of polyamide and maintains this temperature, and then crushes it in a mechanical crusher to obtain polyamide powder. However, the powder prepared by the mechanical crushing method has poor sphericity, irregular morphology, and uneven size distribution, which can easily lead to warping and uneven surface of 3D printed parts.
[0005] Therefore, how to prepare high-flowability polyamide powder suitable for SLS processing by a simple method that combines the advantages of polyamide and polyolefin remains a problem to be solved. Summary of the invention
[0006] In order to solve the aforementioned problems, the object of the present invention is to provide a laser sintering 3D printing polyamide powder.
[0007] In order to achieve the above object, the technical solution specifically provided by the present invention is as follows:
[0008] A laser sintering 3D printing polyamide powder, which is prepared by cryogenic grinding and sieving polyamide particles, characterized in that: the laser sintering 3D printing polyamide powder has a D10 of 20-30 μm, a D50 of 40-55 μm, and a D90 of 80-100 μm as measured by laser diffraction particle size determination method;
[0009] In the process of preparing the polyamide particles, the temperature of deep cold grinding is -100 to -70°C and the grinding speed is 500 to 800 rpm;
[0010] The raw materials for preparing the polyamide particles contain:
[0011] (i) polyamide, wherein the polyamide comprises at least one polyamide A having a brittle temperature of -70 to -30°C and at least one polyamide B having a brittle temperature ≤ -70°C, and the weight ratio of polyamide A to polyamide B is (3-5):5;
[0012] (ii) a polyolefin component, wherein the polyolefin component has a brittle temperature of ≤-70°C, and the polyolefin component is a polyolefin elastomer and / or polyolefin, and the weight ratio of the polyolefin component to the polyamide is 1:(5-10);
[0013] and (iii) reinforcing fibers, wherein the weight ratio of the reinforcing fibers to the polyamide is 1:(5-10).
[0014] By adopting the above technical scheme, polyamide particles are prepared from raw materials mixed with polyamide and polyolefin components with specific brittle temperature characteristics and reinforcing fibers in a specific proportion, and then the polyamide particles are processed into laser sintered 3D printing polyamide powder with a specific particle size distribution by cryogenic grinding. This type of laser sintered 3D printing polyamide powder has the advantages of both polyamide and polyolefin components, with a particle size of ≤100μm and a certain width of particle size distribution. It has good fluidity and filling properties when used for SLS processing. The outer surface of the product obtained by SLS processing is smooth and flat, without internal voids, product warping and other defects.
[0015] Furthermore, the polyamide A is one or more of polyamide 6, polyamide 66, and polyamide 11.
[0016] Furthermore, the polyamide B is polyamide 12.
[0017] Furthermore, the polyolefin is one or more of LDPE, MDPE, MDPE, and UHMWPE; preferably MDPE or UHMWPE.
[0018] Furthermore, the polyolefin elastomer is one or more of ethylene / α-olefin block copolymer, ethylene-butene copolymer, ethylene-hexene copolymer, and ethylene-octene copolymer.
[0019] Furthermore, the reinforcing fiber is one or more of carbon fiber, glass fiber, and mineral fiber. The addition of reinforcing fiber can make up for the deficiencies in mechanical properties of polyolefin components, so that the products obtained by laser sintering 3D printing polyamide powder have sufficient mechanical strength.
[0020] Furthermore, the raw material for preparing the polyamide particles also contains a flame retardant, and the weight ratio of the flame retardant to the polyamide is 1.5:(5-10). By adding the flame retardant in the above ratio, a laser sintering 3D printing polyamide powder with flame retardant properties can be obtained, which broadens its application field.
[0021] Furthermore, the flame retardant is selected from one or more of halogen flame retardants, hydrated metal oxides, organic phosphorus flame retardants, nitrogen flame retardants, and intumescent flame retardants.
[0022] Furthermore, the raw material for preparing the polyamide particles also contains a flow-improving agent, and the weight ratio of the flow-improving agent to the polyamide is 0.5:(5-10).
[0023] Furthermore, the flow improving agent is a mixture of one or more of metal stearate, pentaerythritol grease, and ultra-high molecular weight silicone.
[0024] Furthermore, the raw materials for preparing the polyamide particles also contain polystyrene-divinylbenzene microspheres with a particle size of ≤10 μm, and the weight ratio of the polystyrene-divinylbenzene microspheres to the flame retardant is 1:(0.8-1.2); when preparing the polyamide particles, the polystyrene-divinylbenzene microspheres and the flame retardant are premixed at a speed of 3000-5000 rpm for 15-20 minutes before adding the materials.
[0025] The present invention has the following beneficial effects:
[0026] 1. The present invention mixes polyamide and polyolefin components with specific brittle temperature characteristics with reinforcing fibers to prepare polyamide particles. After cryogenic grinding, a 3D printing polyamide powder suitable for laser sintering with a suitable particle size and a moderate particle size distribution range can be obtained. The outer surface of the product obtained by SLS processing of the 3D printing polyamide powder sintered by laser sintering of the present invention is smooth and flat, without defects such as internal voids and product warping;
[0027] 2. In the preferred embodiment of the present invention, an appropriate amount of flame retardant is added to give the laser sintered 3D printed polyamide powder flame retardant elasticity, which is suitable for SLS processing to obtain flame retardant products, thereby increasing its application field. DETAILED DESCRIPTION
[0028] In order to enable those skilled in the art to better understand the technical solutions of the present invention, the present application will be further described in detail below in conjunction with various preparation examples / embodiments.
[0029] [Preparation of polyamide particles]
[0030] The polyamide and polyolefin components dried to a moisture content of ≤0.3% are put into a screw extruder, and reinforcing fibers, flow modifiers and antioxidants are added and mixed evenly, and melt extruded into granules. The temperature of the feeding section of the screw extruder barrel is 250-260°C, the temperature of the melting section is 260-270°C, and the temperature of the homogenizing section is 260-280°C; the temperature of the connection neck of the mold and the barrel is 220-240°C, and the temperature of the molding mold is 200-210°C.
[0031] Preparation Example 1-6
[0032] The difference between Preparation Examples 1-6 is the different ratios of raw materials, as shown in Table 1.
[0033] Table 1. Raw material ratios of preparation examples 1-6 (by weight)
[0034]
[0035] Among them, polyamide 6 has a brittle temperature of -40 to -32°C and comes from Fujian Xinlong Industrial Co., Ltd.; polyamide 66 has a brittle temperature of -30°C and comes from Hangzhou Polyshun New Materials Co., Ltd.; polyamide 11 (brand Polyamide 11) has a brittle temperature of -40°C and comes from Arkema; polyamide 12 (brand name Kern PA12GB30) has a brittle temperature of -70°C and comes from Dongguan Shuangbang Plastic Raw Materials Co., Ltd.; medium-density polyethylene (MDPE) has a brittle temperature of -70°C and is branded DX800 and comes from Dongguan Tengwang Engineering Plastics Co., Ltd.; ultra-high molecular weight polyethylene (UHMWPE), branded LUBMER TM L4000, from Mitsui Chemicals; POE brittle temperature <-70°C, brand TAFMERA4070S, from Mitsui Chemicals; carbon fiber is Toray T300 chopped carbon fiber (Toray, Japan), with a diameter of 7 μm and an aspect ratio of 100:1. The specific selection of the above raw materials is only an exemplary description and is not a limitation of this application. In other preparation examples, raw materials of other brands, specifications, and sources can be selected according to actual needs.
[0036] Preparation Example 7-9
[0037] Preparation Examples 7-9 are based on Preparation Example 6, except that the raw materials contain flame retardant (Clariant OP1400), see Table 2 for details.
[0038] Table 2. Raw material ratios of Preparation Examples 6-9 (by weight)
[0039]
[0040] The flame retardant can be selected from one or more of halogen flame retardants, hydrated metal oxides, organic phosphorus flame retardants, nitrogen flame retardants, and intumescent flame retardants. Preparation Examples 7-9 are all made of Clariant OP 1400 is used as an example, and other types and brands of flame retardants may be selected in other preparation examples.
[0041] Preparation Example 10-12
[0042] Preparation Examples 10-12 are based on Preparation Example 9, with the difference that: the raw material also contains polystyrene-divinylbenzene microspheres with a particle size of ≤10 μm, and the weight ratio of polystyrene-divinylbenzene microspheres to flame retardant is 1:(0.8-1.2); when preparing polyamide particles, the polystyrene-divinylbenzene microspheres and the flame retardant are premixed at a speed of 3000-5000 rpm for 15-20 minutes and then put into the screw extruder.
[0043] The dosage ratio of the flame retardant and polystyrene-divinylbenzene microspheres in Preparation Examples 10-12 and the premixing process parameters of the two are shown in Table 3.
[0044] Table 3. Amounts of flame retardants and polystyrene-divinylbenzene microspheres (by weight) and premixing process parameters of preparation examples 10-12
[0045]
[0046] Among them, polystyrene-divinylbenzene microspheres (PS-DVB) with an average particle size of 8 μm were obtained from Shanghai Yipuri Biotechnology Co., Ltd. In other preparation examples, polystyrene-divinylbenzene microspheres of other sources and specifications may also be selected.
[0047] Comparative Preparation Examples 1-4
[0048] Comparative Preparation Examples 1-4 are all based on Preparation Example 6, with the difference being that the proportions of raw materials are different, as shown in Table 4 for details.
[0049] Table 4. Raw material ratios of comparative preparation examples 1-4 (by weight)
[0050]
[0051] [Preparation of polyamide powder for laser sintering 3D printing]
[0052] The polyamide particles obtained in the above preparation example were added to a cryogenic pulverizer, liquid nitrogen was introduced, and the cryogenic pulverizer was started for cryogenic grinding. The grinding temperature was -70°C and the grinding speed was 800 rpm. The powder obtained by grinding was passed through a 140 mesh sieve (sieve aperture 104 μm) to obtain laser sintering 3D printing polyamide powder. The initial crystallization temperature and initial melting temperature of the powder were characterized by differential scanning calorimetry (DSC), and the corresponding sintering window was calculated; the particle size distribution of the obtained laser sintering 3D printing polyamide powder was determined by laser diffraction particle size determination; the powder sample was sintered with Hunan Huashu High-Tech HT252 laser sintering equipment to obtain the product, and the smoothness of the product was manually checked, and the presence of cavities inside the product was ultrasonically checked, and the flame retardant properties of the product were measured with reference to the UL-94 flame retardant test.
[0053] Examples 1-6
[0054] In Examples 1-6, the polyamide particles prepared in Preparation Examples 1-6 were used as raw materials to prepare laser sintering 3D printing polyamide powders. The performance test results are shown in Table 5.
[0055] Table 5. Test results 1
[0056]
[0057] It can be seen from the data in Table 5 that the laser sintering 3D printing polyamide powder of the present invention has a small average particle size and a relatively wide particle size distribution. At the same time, the powder has a wide sintering window of 32.4-36.1°C, which makes the powder have good fluidity and filling properties. During the SLS processing, the powder can be better sintered to form products, reducing problems such as internal voids, rough surfaces, and warping of products.
[0058] Embodiment 7-9
[0059] In Examples 7-9, the polyamide particles prepared in Preparation Examples 7-9 were used as raw materials to prepare laser sintering 3D printing polyamide powders. The performance test results are shown in Table 6.
[0060] Table 6. Test results 2
[0061]
[0062] From the data in Table 6, we can see that after adding a certain amount of flame retardant, the powder can be given flame retardant properties, and the flame retardancy of the 1.6mm thick product obtained by processing passes the UL94 V0 test. At the same time, it can be seen from the test data that after adding flame retardant, the sintering window of the powder is only slightly narrowed, and the particle size distribution is slightly narrowed, which does not affect the laser sintering processability of the powder as a whole.
[0063] Examples 10-12
[0064] In Examples 10-12, the polyamide particles prepared in Preparation Examples 10-12 were used as raw materials to prepare laser sintering 3D printing polyamide powders. The performance test results are shown in Table 7.
[0065] Table 7. Test results 3
[0066]
[0067] From the data in Table 7, it can be seen that the addition of polystyrene-divinylbenzene microspheres does not affect the flame retardant performance of the powder, and the flame retardancy of the 1.6mm thick parts obtained by processing passes the UL94 V0 test. At the same time, it can be seen from the test data that after the addition of polystyrene-divinylbenzene microspheres and flame retardant premix, the sintering window of the powder tends to be broadened, the powder particle size distribution range is wide, and D10 / D50 decreases slightly, that is, the proportion of small and medium-sized particles in the powder increases, the powder fluidity and filling properties are better, and the laser sintering processability is better.
[0068] Examples 13-14
[0069] In Examples 13-14, the polyamide particles prepared in Preparation Example 12 were used as raw materials to prepare laser sintering 3D printing polyamide powders, and the difference was that the cryogenic grinding process parameters were different. Specifically, in Example 13, the grinding temperature was -80°C and the grinding speed was 700 rpm; in Example 13, the grinding temperature was -90°C and the grinding speed was 600 rpm; in Example 13, the grinding temperature was -100°C and the grinding speed was 500 rpm. The performance test results are shown in Table 8.
[0070] Table 8. Test results 4
[0071]
[0072] It can be seen from the data in Table 8 that the cryogenic grinding process parameters will affect the particle size of the powder to a certain extent. The lower the grinding temperature, the smaller the powder particle size tends to be, and the powder sintering window is slightly narrowed.
[0073] Comparative Examples 1-4
[0074] Comparative Examples 1-4 respectively used the polyamide particles prepared in Comparative Preparation Examples 1-4 as raw materials to prepare laser sintering 3D printing polyamide powders. The performance test results are shown in Table 9.
[0075] Table 9. Test results 5
[0076]
[0077] It can be seen from the data in Table 9 that: compared with the embodiment, after the raw material ratio of the comparative polyamide particles is changed, the non-sphericity of the powder may increase during the deep cold grinding process, so that although the particle size of the powder obtained in the comparative example is smaller, the particle size distribution range is narrow and the sintering window is significantly narrowed, which is not conducive to the flow and full filling of the powder during powder spreading. It is easy to form defects such as voids inside the workpiece during laser sintering, and it is also not conducive to the laser sintering process to obtain a smooth and warp-free product.
[0078] The above are all preferred embodiments of the present application, and the protection scope of the present application is not limited thereto. Therefore, any equivalent changes made according to the structure, shape, and principle of the present application should be included in the protection scope of the present application.
Claims
1. A laser sintering 3D printing polyamide powder, which is prepared by cryogenic grinding and sieving polyamide particles, characterized in that: The laser sintering 3D printing polyamide powder has a D10 of 20-30 μm, a D50 of 40-55 μm, and a D90 of 80-100 μm as measured by laser diffraction particle size determination method; In the process of preparing the polyamide particles, the temperature of deep cold grinding is -100 to -70°C and the grinding speed is 500 to 800 rpm; The raw materials for preparing the polyamide particles contain: (i) polyamide, wherein the polyamide comprises at least one polyamide A having a brittle temperature of -70 to -30°C and at least one polyamide B having a brittle temperature ≤ -70°C, and the weight ratio of polyamide A to polyamide B is (3-5):5; (ii) a polyolefin component, wherein the polyolefin component has a brittle temperature of ≤-70°C, and the polyolefin component is a polyolefin elastomer and / or polyolefin, and the weight ratio of the polyolefin component to the polyamide is 1:(5-10); and (iii) reinforcing fibers, wherein the weight ratio of the reinforcing fibers to the polyamide is 1:(5-10).
2. The laser sintering 3D printing polyamide powder according to claim 1, characterized in that: The polyamide A is one or more of polyamide 6, polyamide 66, and polyamide 11.
3. The laser sintering 3D printing polyamide powder according to claim 1, characterized in that: The polyamide B is polyamide 12.
4. The laser sintering 3D printing polyamide powder according to claim 1, characterized in that: The polyolefin is one or more of LDPE, MDPE, MDPE and UHMWPE.
5. The laser sintering 3D printing polyamide powder according to claim 1, characterized in that: The polyolefin elastomer is one or more of ethylene / α-olefin block copolymer, ethylene-butene copolymer, ethylene-hexene copolymer and ethylene-octene copolymer.
6. The laser sintering 3D printing polyamide powder according to claim 1, characterized in that: The reinforcing fiber is one or more of carbon fiber, glass fiber and mineral fiber.
7. The laser sintering 3D printing polyamide powder according to any one of claims 1 to 6, characterized in that: The raw material for preparing the polyamide particles also contains a flame retardant, and the weight ratio of the flame retardant to the polyamide is 1.5:(5-10).
8. The laser sintering 3D printing polyamide powder according to claim 7, characterized in that: The flame retardant is selected from one or more of halogen flame retardants, hydrated metal oxides, organic phosphorus flame retardants, nitrogen flame retardants, and intumescent flame retardants.
9. The laser sintering 3D printing polyamide powder according to any one of claims 1 to 6, characterized in that: The raw material for preparing the polyamide particles also contains a flow-improving agent, and the weight ratio of the flow-improving agent to the polyamide is 0.5:(5-10).
10. The laser sintering 3D printing polyamide powder according to claim 9, characterized in that: The flow-improving auxiliary agent is a mixture of one or more of stearic acid metal salt, pentaerythritol grease, and ultra-high molecular weight silicone.
Citation Information
Patent Citations
Carbon fiber reinforced resin powder material for selective laser sintering
CN103951971A
Nylon blended polyethylene powder material for use in selective laser sintering (SLS) and preparation method thereof
CN104164080A
Polymer powder material for selective laser sintering and preparation method thereof
CN118185300A